Isolasi dan karakterisasi senyawa metabolit sekunder dari bakteri laut Streptomyces sp. - Muhammad Bahi (Depik, 2012)
Abstract: Streptomyces is one of bacterial genus which has been considered as a potential source of many novel antibiotics from both terrestrial and marine microorganism. In this paper, four secondary metabolites have been isolated and characterized from a marine Streptomyces sp. B5798, namely phydroxyphenylacetic acid (2), indole-3-carboxylic acid (3), indole-3-acetic acid (4), and Macrolactin A (5), respectively. Two of them are common compounds, namely indole-3-carboxylic acid (3) and indole-3-acetic acid (4). The 3,4 dihydroxybenzaldehyde is a degradation product of phydroxyphenylacetic (2) in microorganism. Macrolactin A (5) showed cytotoxicity against brine shrimps test (A. salina). All structures of the isolated compounds were elucidated based on spectroscopic and mass spectrometry data.